Dandy walker syndrome- a CMF involving brain -case report (International Journal of Scientific Research and Management (IJSRM), 2015)
The Dandy Walker syndrome comprises of congenital brain mal formation involving the cerebellum and the fluid filled spaces around it. It is a disorder of ventral induction resulting in hindbrain abnormalities incorporating varying degrees of cerebellar vermis and/or enlargement of cisterna magna. A case was reported during routine fetal autopsy done in the Department of Anatomy at Government Medical College & Hospital, Chandigarh. It was a male fetus of 19+6 wks. The indication for MTP was Dandy Walker Syndrome detected on ultra sonogram at 27 weeks. In autopsy, there was hypoplasia of cerebellum making floor of fourth ventricle visible and also, right side cerebellar hemisphere was smaller than left. The syndrome is associated with fetal karyotype abnormalities, so amniocentesis can be offered on prenatal diagnosis